High quality DNA from peat soil for metagenomic studies: A minireview on DNA extraction methods - Mohamad Roslan, Muhamad Aidilfitri; Mohamad, Mohd Azrul Naim; Mohd Omar, Suhaila (RAZI Publishing, 2017)
The urge of understanding soil microbial function and diversity of peatland soils either forested or non-forested has emerged since over a decade ago concerning the ongoing the ecosystem deterioration and its environmental impacts it causes. Like any other soil environments, this unique ecosystem possesses great challenges in isolating quality DNA prerequisite for microbial ecology studies in virtue of its physicochemical characteristics. Two general approaches have been extensively applied for soil microbial DNA extraction which are termed as direct DNA extraction protocol and indirect DNA extraction protocol. The only step differentiate between these two protocols is the later includes additional cell separation method from soil microaggregates preceding DNA extraction process. Therefore, several improved and modified methods in conventional DNA extraction and purification methods are reviewed in this paper to cater all the highlighted issues as to obtain high-quality DNA for soil peatland metagenomics studies.